Analisis Perilaku Hidup Bersih dan Sehat (PHBS) pada Masyarakat di Kelurahan Kenangan Kecamatan Percut Sei Tuan Deli Serdang - Nanda, Meutia; Putri, Firsty Alifa; Hana, Nabila; Sonia, Putri; Dalimunthe, Rabiatul Adhwiyah; Husen, Saddam; Sembiring, Sandi Pranata (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Clean and healthy living behavior (PHBS) in household arrangements is an effort that aims to cultivate PHBS in the family scope. Basically good behavior starts from the home environment and family habits in the household. This study aims to determine the application of household PHBS in Kenangan village. The research design used cross sectional with a sample of 78 people, the sample was taken using a simple random sampling technique with an analytical survey design. The data analysis used is by using Chi Square statistical test. Based on the results of the research analysis that has been carried out, it can be concluded that the average female respondent is a housewife so that she can carry out clean and healthy living behaviors properly. The results from respondents regarding smoking habits are quite high in the region. Almost all residents in the area are very good at implementing good and healthy homes. A good and healthy house has adequate ventilation. The results of data analysis showed that the application of exclusive breastfeeding, hand washing with soap, and smoking habits had a positive correlation with age and level of education with a p-value <0.05. Then the relationship between the characteristics of the respondents and the application of trash bins, good latrine conditions, and good housing conditions has a positive correlation with age with a p-value <0.05. It is recommended for health workers to activate health cadres in the Kenanga sub-district in Percut Sei Tuan sub-district, for the community, namely increasing individual, family and community health care by living a clean and healthy life. Keywords: Clean and healthy living behavior, PHBS, household PHBS